IDENTIFIKASI BATAS LATERAL CEKUNGAN AIRTANAH (CAT) PALU - Zeffitni, Zeffitni (SMARTek, 2011)
Groundwater basin naturally constrained by the limits controlled by the hydrogeologic andgeologic conditions or groundwater hydraulics, and in general not the same as the governmentboundaries. The purpose of this study to identify the lateral boundary of Palu Groundwater Basin(CAT Palu). Analysis method based on analysis of field data for the determination of thegeometry and configuration of the lateral aquifer system. The results showed that: 1). externalzero flow boundary, are the contact area between the aquifer and the aquifers that form CATPalu. This form of field boundary fault, conformity and the unconformity as the main geologicalstructures are dominated by graben structures known as Palu Fault, 2). CAT Palu boundarybased on groundwater divide coincides with the boundary surface of the water separatorwhich separates the two main aquifer groundwater flow in the opposite direction, 3). externalhead-controlled boundary in CAT Palu is the sea level because the main aquifer is notdepressed, and 4). inflow boundary located in the east and west of Palu River, from structuralbuckling hillsides and Mount Mount Gawalise Tanggungguno. In the southern part of the PaluRiver upstream Kamamora area. Outflow boundary located in the northern part of the Gulf ofPalu.